The Balinese Local Wisdom “Tri Hita Karana” In Csr Initiatives: Learnings From Aqua Danone-Mambal Plant, Bali Indonesia - Yeni, Rosilawati; Ahmad, Jamilah (2015)
Corporate Social Responsibility (CSR), is a strategic corporate initiatives that receives an increased amount of attention in the business world. CSR in general intends to encourage the businesses to be more ethical in their activities and not to have negative influence on society and the environment. This paper aims to identify the implementation of CSR in Aqua Danone by incorporating local wisdom which was carried out in the local community who lives around the operating factory of Aqua Mambal Plant, Bali, Indonesia In 2015, Aqua Danone Group achieved 8 platinums, 4 golds and 1 silver awards on 2015 by the ministry of Human Development & Culture in recognition of their support to Millenium Development Goals (MDG) in Indonesia. Their programs such as WASH (Water Access Sanitation & Hygiene) in Klaten, Central Java Province, Coopmart for Farmers in Bogor Region, and Water Conservation in Badung- Bali were highly recognized because of empowering local communities and contribute to environment. This paper used a qualitative approach, case study method. It employed in-depth interviews which were conducted with the local communities and working managers who deal with CSR issues and strategy on day-to-day basis. Secondary data was also gathered in the form of information about CSR program from sustainable reports in the company’s website, media news that were downloaded from the internet as well as from other. The researchers hope to be able to incorporating the value of local wisdom in the CSR Model.